Assessing the impact of community-based homestay experiences on tourist loyalty in sustainable rural tourism development - Qiwen Dai; Jinglian Chen; Yanqiao Zheng (Scientific Reports)
Abstract In the context of community-based tourism, this study investigates the determinants of tourist loyalty to homestays, with a focus on sustainable rural tourism development in China. Using the stimulus–organism–response (SOR) framework, we propose a conceptual model to examine how connected experiences influence tourist emotions and, in turn, their loyalty. Data were gathered through onsite surveys of tourists, and structural equation modeling was applied to assess the relationships between key variables. The analysis reveals that tourists’ emotions mediate the effect of connected experiences on loyalty, while the unique local characteristics of homestays significantly moderate the link between emotions and loyalty. These findings provide valuable insights for policymakers and practitioners aiming to enhance the sustainability of rural tourism through strategic management of community-based homestays.